Preparation method and application of material for screening cyclooxygenase-2 inhibitor
Through Fe3O4@MWCNTs@PDA-Cu2+ magnetic composite nanoparticles, the problems of low efficiency and reduced enzyme activity in traditional methods are solved, and a method of efficient screening of cyclooxygenase-2 inhibitors is realized. High sensitivity and stability.
Patent Information
- Application Number
- CN202411403998.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
AI Technical Summary
Traditional Chinese medicine extraction and isolation methods are inefficient, making it difficult to screen out cyclooxygenase-2 inhibitors, and enzyme fixation methods can easily lead to reduced enzyme activity and sensitivity.
Fe3O4@MWCNTs@PDA-Cu2+ magnetic composite nanoparticles were used to fix cyclooxygenase-2 using Cu2+ as an affinant, and the Fe3O4 nanoparticles were coated by surface modification of multi-walled carbon nanotubes and polydopamine to maintain the spatial configuration of the enzyme. Stabilize and improve enzyme activity.
Efficient, specific and sensitive cyclooxygenase-2 inhibitor screening was achieved, maintaining the activity of the enzyme and reducing metal ion leakage and protein load limit in traditional methods.
Smart Images

Figure CN119291174A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanomaterials, and in particular relates to a preparation method and application of a material for screening a cyclooxygenase-2 inhibitor. Background Art
[0002] The occurrence of chronic inflammation can lead to the disorder of the body's immune system, promote the aggravation of inflammatory response and tissue damage, and long-term chronic inflammation can lead to the occurrence and development of chronic diseases such as cancer, arthritis, diabetes, cardiovascular disease and nervous system diseases. Although the currently available cyclooxygenase-2 inhibitors such as meloxicam and celecoxib can effectively treat inflammation and have fewer side effects compared with traditional non-steroidal anti-inflammatory drugs such as aspirin, they still have the risk of causing liver and kidney toxicity, cardiovascular disease, etc. A large number of studies have shown that the active ingredients such as alkaloids, coumarins, flavonoids, and saponins in Chinese herbal medicines have good anti-inflammatory effects and have the characteristics of small toxic and side effects. Therefore, screening potential cyclooxygenase-2 inhibitors from Chinese herbal medicines is of great significance for the development of safe and effective new anti-inflammatory drugs. However, the traditional extraction and separation methods of Chinese herbal medicines usually require multiple separations and purifications to screen the target ingredients from many complex Chinese herbal medicine ingredients. Not only is the workload large, time-consuming, and inefficient, but some potential trace active ingredients may also be missed.
[0003] The magnetic ligand fishing method uses magnetic nanomaterials (MNPs) with functional groups on the surface as carriers, and immobilizes the target protease on MNPs by adsorption, embedding, cross-linking or covalent bonding for ligand fishing. However, the above enzyme immobilization methods are prone to lead to problems such as stacking or embedding between enzyme molecules, reduced enzyme activity, decreased sensitivity to ligands, and reduced sensitivity of capturing ligands. Therefore, it is necessary to develop a new enzyme immobilization method to maintain the activity of the enzyme to ensure high efficiency of fishing targets. Summary of the invention
[0004] In order to solve the above problems in the prior art, the present invention provides a material for screening cyclooxygenase-2 inhibitors, wherein the material is a magnetic composite nanoparticle immobilized with cyclooxygenase-2, and the expression of the magnetic composite nanoparticle is Fe 3 O 4 @MWCNTs@PDA-Cu 2+ The magnetic composite nanoparticles are loaded with Fe 3 O 4 Nanoparticles of multi-walled carbon nanotubes coated with chelated Cu 2+ of polydopamine.
[0005] In some feasible embodiments, Fe 3 O 4The Fe in the nanoparticles is derived from ferric nitrate nonahydrate, and the mass ratio of ferric nitrate nonahydrate to multi-walled carbon nanotubes is 3-6:1, for example, 3-4:1, 4-5:1 or 5-6:1.
[0006] In some feasible examples, the polydopamine and the loaded Fe 3 O 4 The mass ratio of the multi-walled carbon nanotubes to the nanoparticles is 1 to 2:1.
[0007] In some feasible examples, the Cu 2+ The mass ratio of the magnetic nanoparticles to the magnetic composite nanoparticles is 0.0001 to 0.01:1, for example, 0.0001 to 0.001:1, 0.001 to 0.005:1 or 0.005 to 0.01:1.
[0008] In some feasible examples, the Fe 3 O 4 The particle size of nanoparticles is 50 to 100 nm, generally referring to an average particle size of 50 to 100 nm.
[0009] In some feasible examples, the specific surface area of the magnetic composite nanoparticles is 100 to 130 m 2 / g, pore diameter is 20-26nm, pore volume is 0.5-0.8cm 3 / g.
[0010] The second aspect of the present invention provides a method for preparing a material for screening a cyclooxygenase-2 inhibitor, comprising the following steps:
[0011] 1) Provide load Fe 3 O 4 Nanoparticles of multi-walled carbon nanotubes, expressed as Fe 3 O 4 @MWCNTs;
[0012] Specifically, in step 1), ferric nitrate nonahydrate and multi-walled carbon nanotubes are dispersed in an alcohol solvent, and then anhydrous sodium acetate is added, and after ultrasonic dissolution, stirring is performed at room temperature for 20 to 40 minutes, and then reacting at 160 to 220° C. for 12 to 16 hours, standing and cooling to room temperature, and separating solid particles using a magnet, washing with deionized water and anhydrous ethanol in turn, and drying to obtain Fe 3 O 4 @MWCNTs.
[0013] More specifically, the reaction is carried out in a polytetrafluoroethylene-lined reactor, and the reactor is placed in an oven.
[0014] More specifically, the mass ratio of ferric nitrate nonahydrate to multi-walled carbon nanotubes is 3 to 6:1, such as 3 to 4:1, 4 to 5:1 or 5 to 6:1.
[0015] More specifically, the mass ratio of the anhydrous sodium acetate to the multi-walled carbon nanotubes is 8 to 12:1, such as 8 to 10:1, 10 to 11:1, or 11 to 12:1.
[0016] More specifically, the alcohol solvent is ethanol or ethylene glycol.
[0017] 2) Fe 3 O 4 @MWCNTs were dispersed in Tris-HCl buffer, and then dopamine hydrochloride was added to the mixture. After stirring at room temperature for 6 to 24 hours, magnetic separation was performed, and after washing, the mixture was dried in a vacuum oven at 40 to 60°C to obtain Fe 3 O 4 @MWCNTs@PDA;
[0018] Specifically, in step 2), the buffer is a Tris-HCl buffer, the concentration of the buffer is 0.2-1 mg / mL, and the pH is 8.0-8.6. For example, 0.2-0.5 mg / mL or 0.5-1 mg / mL. The pH may be 8.0-8.2, 8.2-8.4, or 8.4-8.6.
[0019] More specifically, the dopamine hydrochloride and the loaded Fe 3 O 4 The mass ratio of the multi-walled carbon nanotubes is 1 to 2:1, such as 1 to 1.5:1 or 1.5 to 2:1.
[0020] More specifically, the cleaning is performed using ultrapure water and anhydrous ethanol for 2 to 6 times respectively.
[0021] 3)Fe 3 O 4 @MWCNTs@PDA was dispersed in a copper salt solution, stirred at room temperature for 6 to 24 hours, and then magnetically separated. After washing, it was dried in a vacuum oven at 40 to 60 °C to obtain a solution of the formula Fe 3 O 4 @MWCNTs@PDA-Cu 2+ Magnetic composite nanoparticles;
[0022] Specifically, in step 3), the copper salt solution is a copper nitrate solution, and the concentration of the copper salt solution is 0.5 to 3.0 mg / mL, such as 0.5 to 1.0 mg / mL, 1.0 to 1.5 mg / mL, 1.5 to 2.0 mg / mL, 2.0 to 2.5 mg / mL or 2.5 to 3.0 mg / mL.
[0023] More specifically, the cleaning is performed using ultrapure water and anhydrous ethanol for 2 to 6 times respectively.
[0024] 4) Immobilizing cyclooxygenase-2 on magnetic composite nanoparticles to obtain materials for screening cyclooxygenase-2 inhibitors.
[0025] Specifically, Fe 3 O 4 @MWCNTs@PDA-Cu 2+ Disperse in a buffer solution, then add a buffer solution containing cyclooxygenase-2 and mix evenly, incubate at 4-12°C for 1-3 hours, and collect the Fe2+-fixed cyclooxygenase-2 by magnetic separation. 3 O 4 @MWCNTs@PDA-Cu 2+ , and washed with ultrapure water to remove unreacted components to obtain a material for screening cyclooxygenase-2 inhibitors. For example, the temperature can be 4-8°C or 8-12°C, and the incubation time can be 1-2h or 2-3h.
[0026] More specifically, the buffer is a Tris-HCl buffer, the concentration of the buffer is 5-15 mmol / L, and the pH is 7.8-8.2. The concentration can be 5-10 mmol / L or 10-15 mmol / L, and the pH can be 7.8-8.0 or 8.0-8.2.
[0027] More specifically, Fe 3 O 4 @MWCNTs@PDA-Cu 2+ The mass ratio of cyclooxygenase-2 is 3 to 8 × 10^ 3 :1, for example 3 to 4×10^ 3 :1,4~5×10^ 3 :1, 5~6×10^ 3 :1,6~7×10^ 3 :1 or 7~8×10^ 3 :1.
[0028] The third aspect of the present invention provides the use of the material for screening cyclooxygenase-2 inhibitors according to the first aspect, or the material for screening cyclooxygenase-2 inhibitors prepared by the preparation method according to the second aspect in screening cyclooxygenase-2 inhibitor materials, or in screening cyclooxygenase-2 inhibitor materials in conjunction with chromatography.
[0029] The present invention has the following technical effects including but not limited to:
[0030] 1) The present invention introduces Cu on the surface of magnetic nanomaterials 2+ The affinity fixation of cyclooxygenase-2 effectively maintains the stability of the spatial configuration of cyclooxygenase-2, thereby maintaining the activity of the enzyme. 2+The chelating agent effectively solves the problems of easy leakage of metal ions and limited protein loading capacity caused by traditional chelating agents.
[0031] 2) The present invention uses Cu 2+ Fixing COX-2 and using it for screening COX-2 inhibitors effectively maintains the activity of the enzyme and has the characteristics of high fishing efficiency, strong specificity and high sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 For example Fe of the present invention 3 O 4 @MWCNTs@PDA-Cu 2+ Electron microscope photos of Fe 3 O 4 @MWCNTs@PDA-Cu 2+ SEM images of (a: low magnification, b: high magnification), (c) and (d) are Fe 3 O 4 @MWCNTs@PDA-Cu 2+ TEM images (c: low magnification, d: high magnification);
[0033] Figure 2 For example Fe of the present invention 3 O 4 @MWCNTs@PDA-Cu 2+ FT-IR characterization diagram of
[0034] Figure 3 For example Fe of the present invention 3 O 4 @MWCNTs@PDA-Cu 2+ XPS analysis diagram, where (a) is a wide spectrum scan diagram, and (b-f) are narrow spectrum scan diagrams of each element;
[0035] Figure 4 For the invention embodiment Fe 3 O 4 @MWCNTs@PDA-Cu 2+ BET analysis diagram of N 2 (b) is the adsorption / desorption curve, and (b) is the pore size distribution diagram.
[0036] Figure 5 In application examples 1 to 5, Fe 3 O 4 @MWCNTs@PDA-Cu 2+ @Fishing efficiency diagram of cyclooxygenase-2 (Cu 2+ concentration effect).
[0037] Figure 6For Application Examples 6 to 9, Fe 3 O 4 @MWCNTs@PDA-Cu 2+ @Fishing efficiency diagram of cyclooxygenase-2 (effect of sample volume).
[0038] Figure 7 In Application Examples 10 to 14, Fe 3 O 4 @MWCNTs@PDA-Cu 2+ @Fishing efficiency diagram of cyclooxygenase-2 (culture temperature).
[0039] Figure 8 In Application Examples 15 to 18, Fe 3 O 4 @MWCNTs@PDA-Cu 2+ @Fishing efficiency diagram of cyclooxygenase-2 (elution reagent concentration).
[0040] Fig. 9 This is the total ion chromatogram obtained in Application Example 19.
[0041] Fig.10 This is the total ion chromatogram obtained in Application Example 20. DETAILED DESCRIPTION
[0042] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0043] It should be noted that the experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified. The process equipment or devices not specifically specified in the following examples are all conventional in the art.
[0044] The multi-walled carbon nanotubes used in Example 1 were purchased from Beijing Solebow Technology Co., Ltd., with the following specifications: purity 95%, length 10-30 microns, and diameter <8 nm.
[0045] The buffer used for washing or storage in all the embodiments that is not specifically described is 0.01 mol / L Tris-HCl buffer with pH=8.0.
[0046] Example 1
[0047] 1) Disperse 2.09g of ferric nitrate nonahydrate and 0.4g of multi-walled carbon nanotubes in 75mL of ethylene glycol, disperse them evenly by ultrasonication, then add 3.6g of anhydrous sodium acetate, dissolve them by ultrasonication, stir them at room temperature for 30min, transfer them to a polytetrafluoroethylene-lined reactor after stirring evenly, place them in an oven at 200℃ for 13h, wait for the reaction to end, and let them stand and cool to room temperature. Use a magnet to separate the solid particles, wash them three times with deionized water and anhydrous ethanol in turn, and dry them to obtain Fe 3 O 4 @MWCNTs.
[0048] 2) Weigh 400 mg of the dried Fe 3 O 4 MWCNTs were dispersed in 250 mL Tris-HCl buffer (0.5 mg / mL, pH = 8.5) and magnetically stirred for 5 min. Then, 500 mg of dopamine hydrochloride (DA) was added to the mixture. After stirring at room temperature for 12 h, magnetic separation was performed. The mixture was washed with ultrapure water and anhydrous ethanol for 3 times and dried in a vacuum oven at 50 °C to obtain Fe 3 O 4 @MWCNTs@PDA.
[0049] 3) 200 mg of the dried Fe 3 O 4 @MWCNTs@PDA was dispersed in 200 mL of copper nitrate solution (1.5 mg / mL), magnetically stirred at room temperature for 12 h, and washed several times with ultrapure water after magnetic separation until the supernatant was colorless and clear, and dried in a vacuum oven at 50 °C to obtain Fe 3 O 4 @MWCNTs@PDA-Cu 2+ Composite nanomaterials.
[0050] 4) Weigh 2 mg Fe 3 O 4 @MWCNTs@PDA-Cu 2+ Dispersed in Tris-HCl buffer (10 mM, pH 8.0), sonicated for 5 min, then added 1.5 mL of Tris-HCl buffer containing cyclooxygenase-2 (0.32 μg / mL) and vortexed for 1 min to disperse evenly, and then shaken at 8 ° C for 2 h. The Fe immobilized cyclooxygenase-2 was collected by magnetic separation. 3 O 4 @MWCNTs@PDA-Cu 2+ , washed with ultrapure water to remove unreacted components, and the expression Fe 3 O 4 @MWCNTs@PDA-Cu 2+@Cyclooxygenase-2 is used to screen cyclooxygenase-2 inhibitor materials and is stored in Tris-HCl buffer solution at 4°C until use. The concentration of the material in the buffer solution is 2 mg / mL.
[0051] Material Characterization:
[0052] 1) Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to investigate the Fe 3 O 4 @MWCNTs@PDA-Cu 2+ The morphology, size, structure, etc. of the Figure 1 As shown, (a) and (b) are Fe 3 O 4 @MWCNTs@PDA-Cu 2+ SEM image, we can see Fe 3 O 4 Nanoparticles are loaded on multi-walled carbon nanotubes with a diameter of 50 to 100 nm. (c) and (d) are Fe 3 O 4 @MWCNTs@PDA-Cu 2+ TEM images show that the core-shell structure of the nanoparticles is clearly visible, and the edges of the multi-walled carbon nanotubes are not smooth and the thickness is uneven, indicating that the PDA is successfully coated and the Cu 2+ of successful chelation.
[0053] 2) Fe was detected by Fourier transform infrared spectroscopy 3 O 4 @MWCNTs@PDA-Cu 2+ The chemical structure of Figure 2 As shown, 1558cm -1 The absorption peak at 565cm is the CC contraction vibration peak, which is the characteristic vibration peak of the graphite structure of carbon nanotubes. -1 There is an obvious Fe-O peak at 3 O 4 Successfully loaded on multi-walled carbon nanotubes. 1383cm -1 、1095cm -1 They are the stretching vibration peak of NH on the PDA surface and the CO absorption peak, respectively, indicating the presence of PDA in the material.
[0054] 3) Fe 3 O 4 @MWCNTs@PDA-Cu 2+ The chemical elements and their valence states in the Figure 3As shown in the results of wide spectrum and narrow spectrum scanning, characteristic peaks corresponding to C1s, N 1s, O 1s, Fe 2p, and Cu 2p can be seen, indicating that Fe 3 O 4 、PDA、Cu 2+ The existence of etc. proves the successful synthesis of the material.
[0055] 4) Analyze Fe by surface area and porosity analyzer 3 O 4 @MWCNTs@PDA-Cu 2+ The surface area and surface pore size of the Figure 4 As shown, (a) is the N of the material 2 The adsorption-desorption curve is a type II isotherm, indicating that the adsorption process is non-porous or macroporous. The specific surface area calculated by the BET method is 122.74 m 2 / g, and the pore volume calculated by BJH method is about 0.64cm 3 / g. The pore size distribution is shown in Figure (b). The surface of the material is mostly mesoporous structure with a pore size of about 24.8nm.
[0056] Example 2
[0057] The difference from Example 1 is that the concentration of the copper nitrate solution in step 3) is 0.5 mg / mL.
[0058] Example 3
[0059] The difference from Example 1 is that the concentration of the copper nitrate solution in step 3) is 1.0 mg / mL.
[0060] Example 4
[0061] The difference from Example 1 is that the concentration of the copper nitrate solution in step 3) is 2.0 mg / mL.
[0062] Example 5
[0063] The difference from Example 1 is that the concentration of the copper nitrate solution in step 3) is 3.0 mg / mL.
[0064] Application Example 1
[0065] Celecoxib, a specific inhibitor of cyclooxygenase-2, was used as the fishing target. The concentration of celecoxib in the eluate was determined by high performance liquid chromatography (HPLC). The fishing efficiency was calculated based on the content of celecoxib in the solution before and after fishing, and the effects of different factors on the fishing efficiency were investigated. The fishing efficiency calculation formula is as follows:
[0066]
[0067] Where C is the concentration of celecoxib in the eluent, mg / mL; V is the volume of the eluent, mL; C 0 is the concentration of celecoxib solution before fishing, mg / mL; V 0 is the volume of celecoxib solution before fishing, mL.
[0068] 9 μL of 5 mg / mL celecoxib DMSO solution was added to 200 μL of 2 mg / mL Fe-2+ immobilized cyclooxygenase-2 prepared in Example 1. 3 O 4 @MWCNTs@PDA-Cu 2+ Buffer solution was added and cultured at 35°C with continuous shaking for 60 min. The microspheres were collected by magnetic separation (the microspheres were Fe 3 O 4 @MWCNTs@PDA-Cu 2+ @cyclooxygenase-2 fishing its fishing target celecoxib microspheres), washed three times with buffer. Then incubated in 400μL of pure methanol for 10min to elute celecoxib specifically bound to the material for screening cyclooxygenase-2 inhibitors, and obtained methanol eluate, and finally the methanol eluate was analyzed by HPLC, chromatographic conditions: chromatographic column is Symmetry C18 (250mm×4.6mm, 5μm); mobile phase: 0~8min, water-methanol (15:85); column temperature is 25℃; flow rate is 1mL / min; injection volume is 10μL; detection wavelength is 254nm.
[0069] Application Examples 2 to 5
[0070] The material of Example 1 in Application Example 1 was replaced with the materials prepared in Examples 2 to 5 respectively.
[0071] like Figure 5 As shown, Cu 2+ The concentration of Fe 3 O 4 @MWCNTs@PDA-Cu 2+ @Cyclooxygenase-2 has a more obvious effect on the fishing efficiency, as Cu 2+ With the increase of concentration, the fishing efficiency gradually increased, reaching the highest at 1.5 mg / mL, and 2+ When the concentration was 3 mg / mL, the fishing efficiency decreased, indicating that Cu 2+ At higher concentrations, the PDA layer may be damaged and Cu may not be efficiently chelated. 2+ , resulting in less immobilized cyclooxygenase-2 and reduced fishing efficiency.
[0072] Application Examples 6 to 9
[0073] The Fe obtained in Example 1 was selected 3 O 4 @MWCNTs@PDA-Cu 2+ @Cyclooxygenase-2 material, an application experiment was carried out, which was different from Application Example 1 in that the volume of the celecoxib DMSO solution (5 mg / mL) as a sample was 3, 6, 12 or 15 μL, respectively.
[0074] The effects of different sample volumes on Fe 3 O 4 @MWCNTs@PDA-Cu 2+ @ The effect of COX-2 on fishing efficiency, such as Figure 6 As shown, with the increase of sample volume, the fishing efficiency was the highest when the sample volume was 9 μL, and decreased when the sample volume increased to 12 and 15 μL. It is speculated that the large sample volume may affect the activity of immobilized cyclooxygenase-2, resulting in a decrease in the sample adsorption amount.
[0075] Application Examples 10-14
[0076] The Fe obtained in Example 1 was selected 3 O 4 @MWCNTs@PDA-Cu 2+ @Cyclooxygenase-2 material was used for application experiments. The difference from Application Example 1 was that the culture temperatures were 20, 25, 30 and 40°C, respectively.
[0077] like Figure 7 As shown, the temperature has an influence on Fe 3 O 4 @MWCNTs@PDA-Cu 2+ @The effect of cyclooxygenase-2 on fishing efficiency is more obvious. The fishing efficiency increases with the increase of temperature and increases sharply at 35℃. When the temperature rises to 40℃, the fishing efficiency decreases sharply, indicating that 35℃ is the optimal temperature for fishing, and higher temperature will affect the activity of cyclooxygenase-2, resulting in lower fishing efficiency.
[0078] Application Examples 15-18
[0079] The Fe obtained in Example 1 was selected 3 O 4 @MWCNTs@PDA-Cu 2+ @Cyclooxygenase-2 material was used for application experiments. The difference from Application Example 1 was that the elution reagents were 60%, 70%, 80% and 90% methanol aqueous solutions.
[0080] like Figure 8As shown, when the methanol ratio increased from 60% to 90%, the fishing efficiency increased but not significantly. When pure methanol was used for elution, the fishing efficiency increased significantly, indicating that pure methanol can effectively promote the breaking of the bond between cyclooxygenase-2 and the target.
[0081] Application Example 19
[0082] The Fe obtained in Example 1 was selected 3 O 4 @MWCNTs@PDA-Cu 2+ @Cyclooxygenase-2 material, application of screening cyclooxygenase-2 inhibitors in total saponins of Panax notoginseng leaves, preparation method of total saponins extract of Panax notoginseng leaves is:
[0083] Weigh 1kg of dried Panax notoginseng leaves, cut into pieces, add 10L 50% ethanol, heat and reflux to extract 3 times (3 times for 3h, 2h, 2h respectively), combine the filtrates, and recover the solvent under reduced pressure to obtain a concentrated Panax notoginseng leaf extract. After the crude extract is adsorbed on macroporous resin D101 for 12h, it is eluted with water, 30% ethanol, and 80% ethanol in sequence, and the 80% ethanol eluate is collected and dried under reduced pressure to obtain the total saponin powder of Panax notoginseng leaves. Weigh 500mg of total saponin powder, add 25mL methanol to dissolve, and prepare 0.02g / mL Panax notoginseng leaf total saponin extract for standby use.
[0084] Take 10 μL of total saponin extract from Panax notoginseng leaves and mix with Fe 2+ obtained in Example 1 and stored in Tris-HCl buffer solution. 3 O 4 @MWCNTs@PDA-Cu 2+ @cyclooxygenase-2 materials were mixed, vortexed and dispersed evenly, and cultured at 35°C for 1 hour. The microspheres were collected by magnetic separation and washed three times with buffer. Then they were incubated in 400 μL of pure methanol for 10 minutes to elute the specifically bound compounds and obtain the fishing eluate. Finally, the fishing eluate was subjected to high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (HPLC-Q-TOF-MS) to analyze the composition and structure of the compounds, and the total saponin extract of Panax notoginseng leaves was also analyzed by high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (HPLC-Q-TOF-MS).
[0085] The total ion chromatogram of liquid-mass mass spectrometry was as follows: Fig. 9 As shown in the figure, A is the total saponin extract of Panax notoginseng leaves, and B is the fishing eluate. By comparison, it was finally determined that 13 saponin components were fished out from the total saponin extract of Panax notoginseng leaves. The molecular mass, fragment ion peak and other information of each peak were compared with the standard, and the information of each compound was shown in Table 1.
[0086] Table 1 Names and structural information of 13 saponins in fishing liquid
[0087]
[0088]
[0089] Application Example 20
[0090] The same method as in Application Example 19 is adopted, except that the total saponin extract of Panax notoginseng leaves is replaced with American ginseng extract. The preparation method of American ginseng extract is as follows:
[0091] Weigh 40g of American ginseng, grind it in a mortar, add 500mL of 80% ethanol, extract it by ultrasonic for 1h, filter it with gauze, and dry the filtrate under reduced pressure to obtain the American ginseng crude extract powder. Weigh 50mg of the sample accurately, dissolve it in methanol, transfer it to a 10mL volumetric flask to make up the volume, and prepare a 5mg / mL American ginseng sample solution for later use.
[0092] UPLC-Q-TOF-MS was used to analyze the American ginseng extract ( Fig.10 A) and the eluate after fishing ( Fig.10 B) were separated to obtain five saponin components, which may be potential COX-2 inhibitors. The names and mass spectrometry information of each compound are shown in Table 2.
[0093] Table 2 Names and structural information of five saponins in fishing liquid
[0094]
[0095]
[0096] Methodological investigation:
[0097] 1. Linear relationship investigation
[0098] A certain amount of celecoxib was weighed and added to the total saponin extract of Panax notoginseng leaves (0.02 g / mL) prepared in Application Example 19 to prepare standard solutions with celecoxib concentrations of 0.0125, 0.0625, 0.125, 0.25, 0.375, 0.625, 1.125, 1.5, and 2.125 mg / mL, respectively. 90 μL of the Fe 2+ solution stored in Tris-HCl buffer solution in Example 1 was taken and added to the standard solutions. 3 O 4 @MWCNTs@PDA-Cu 2+ The materials of @cyclooxygenase-2 were mixed, vortexed and dispersed evenly, and cultured at 35°C for 1 hour. The microspheres were collected by magnetic separation and washed three times with buffer. Then, the eluate was incubated in 400 μL of pure methanol for 10 minutes and analyzed by HPLC. The standard curve was drawn with the concentration as the ordinate and the peak area as the ordinate. The linear equation was Y=1.3×10 5+5.34×10 6 X, R 2 =0.9995.
[0099] 2. Detection limit investigation
[0100] The eluate obtained by treatment with 0.0125 mg / mL was injected 11 times simultaneously. The detection limit (LOD) was calculated from the peak area obtained by detection to be 0.002 mg / mL, and the quantification limit (LOQ) was 0.007 mg / mL. The calculation formula was LOD=3SD / k, LOQ=10SD / k, where SD was the standard deviation of the peak area values measured by 11 injections, and k was the slope of the linear regression equation.
[0101] 3. Precision inspection
[0102] Intra-day precision: 90 μL of 0.625 mg / mL standard solution was accurately pipetted, 6 eluates were prepared in parallel, and the samples were injected and the contents were determined simultaneously within one day. The calculated RSD value was 1.7%.
[0103] Inter-day precision: Pipette 90 μL of the standard solution with a concentration of 0.625 mg / mL, prepare 6 eluates in parallel, and measure the content by injection for 6 consecutive days. The RSD value is calculated to be 2.5%.
[0104] The RSD values of intra-day and inter-day precision were both less than 3%, indicating that the method had good precision.
[0105] 4. Stability inspection
[0106] Accurately pipette 90 μL of 0.625 mg / mL standard solution to obtain the eluate, and inject the sample at 0, 2, 4, 6, 8, and 10 h, respectively. The concentration is calculated from the measured peak area value, and the RSD value is 2.1%, indicating that the sample has good stability within 10 h.
[0107] 5. Repeatability test
[0108] 90 μL of the standard solution with a concentration of 0.625 mg / mL was taken for parallel treatment to obtain 6 eluates, which were respectively subjected to HPLC analysis to determine their concentrations. The RSD value was calculated to be 2.3%, indicating that the method had good repeatability.
[0109] 6. Sample recovery test
[0110] Celecoxib solutions at three concentration levels, low, medium and high, were added to the Panax notoginseng leaf extract, and the eluents were prepared separately. Three parallel preparations were made for each concentration. The content of each sample was determined by HPLC, and the recovery rate of celecoxib was calculated to be 82.3% to 98.2%, with RSD values between 1.1% and 3.2%, indicating that the method has good accuracy and applicability.
[0111] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A material for screening cyclooxygenase-2 inhibitors, characterized in that: The material is a magnetic composite nanoparticle fixed with cyclooxygenase-2, and the expression of the magnetic composite nanoparticle is Fe3O4@MWCNTs@PDA-Cu 2+ The magnetic composite nanoparticles are multi-walled carbon nanotubes loaded with Fe3O4 nanoparticles and coated with chelated Cu 2+ of polydopamine.
2. The material for screening cyclooxygenase-2 inhibitors according to claim 1, characterized in that: The Fe in the Fe3O4 nanoparticles is derived from ferric nitrate nonahydrate, and the mass ratio of ferric nitrate nonahydrate to multi-walled carbon nanotubes is 3-6:1; And / or, the mass ratio of the polydopamine to the multi-walled carbon nanotubes loaded with Fe3O4 nanoparticles is 1 to 2:1; and / or, the Cu 2+ The mass ratio of the composite magnetic nanoparticles is 0.0001 to 0.01:1; And / or, the Fe3O4 nanoparticles have a particle size of 50 to 100 nm; And / or, the specific surface area of the magnetic composite nanoparticles is 100 to 130 m 2 / g, pore diameter is 20-26nm, pore volume is 0.5-0.8cm 3 / g.
3. A method for preparing a material for screening a cyclooxygenase-2 inhibitor, comprising the following steps: 1) providing multi-walled carbon nanotubes loaded with Fe3O4 nanoparticles, expressed as Fe3O4@MWCNTs; 2) Dispersing Fe3O4@MWCNTs in Tris-HCl buffer, then adding dopamine hydrochloride to the mixture, stirring at room temperature for 6 to 24 hours, and then magnetically separating, washing, and drying in a vacuum drying oven at 40 to 60°C to obtain Fe3O4@MWCNTs@PDA; 3) Fe3O4@MWCNTs@PDA was dispersed in a copper salt solution, stirred at room temperature for 6 to 24 hours, and then magnetically separated. After washing, the solution was dried in a vacuum oven at 40 to 60°C to obtain Fe3O4@MWCNTs@PDA-Cu 2+ Magnetic composite nanoparticles; 4) Immobilizing cyclooxygenase-2 on magnetic composite nanoparticles to obtain materials for screening cyclooxygenase-2 inhibitors.
4. The method for preparing a material for screening a cyclooxygenase-2 inhibitor according to claim 3, characterized in that: In step 1), ferric nitrate nonahydrate and multi-walled carbon nanotubes are dispersed in an alcohol solvent, and then anhydrous sodium acetate is added, and after ultrasonic dissolution, the mixture is stirred at room temperature for 20 to 40 minutes, and then reacted at 160 to 220° C. for 12 to 16 hours, and allowed to stand and cool to room temperature. Solid particles are separated using a magnet, and then washed with deionized water and anhydrous ethanol in turn, and dried to obtain Fe3O4@MWCNTs.
5. The method for preparing a material for screening a cyclooxygenase-2 inhibitor according to claim 4, characterized in that: The reaction is carried out in a polytetrafluoroethylene-lined reactor, which is placed in an oven; and / or, the mass ratio of ferric nitrate nonahydrate to multi-walled carbon nanotubes is 3 to 6:1; And / or, the mass ratio of the anhydrous sodium acetate to the multi-walled carbon nanotubes is 8 to 12:1; And / or, the alcohol solvent is ethanol or ethylene glycol.
6. The method for preparing materials for screening cyclooxygenase-2 inhibitors according to claim 3, characterized in that: In step 2): The buffer is a Tris-HCl buffer, the concentration of the buffer is 0.2-1 mg / mL, and the pH is 8.0-8.6; The mass ratio of dopamine hydrochloride to the Fe3O4-loaded multi-walled carbon nanotubes is 1 to 2:1; The samples were cleaned with ultrapure water and anhydrous ethanol for 2 to 6 times respectively.
7. The method for preparing a material for screening a cyclooxygenase-2 inhibitor according to claim 3, characterized in that: In step 3): The copper salt solution is a copper nitrate solution, and the concentration of the copper salt solution is 0.5 to 3.0 mg / mL; The samples were cleaned with ultrapure water and anhydrous ethanol for 2 to 6 times respectively.
8. The method for preparing a material for screening a cyclooxygenase-2 inhibitor according to claim 3, characterized in that: In step 4), Fe3O4@MWCNTs@PDA-Cu 2+ Dispersed in a buffer solution, then a buffer solution containing cyclooxygenase-2 was added and mixed evenly, incubated at 4-12°C for 1-3 h, and the Fe3O4@MWCNTs@PDA-Cu2 immobilized cyclooxygenase-2 was collected by magnetic separation. 2+ , washed with ultrapure water to remove unreacted components, and obtained a material for screening cyclooxygenase-2 inhibitors.
9. The method for preparing a material for screening a cyclooxygenase-2 inhibitor according to claim 8, characterized in that: The buffer is a Tris-HCl buffer, the concentration of the buffer is 5 to 15 mmol / L, and the pH is 7.8 to 8.2; Fe3O4@MWCNTs@PDA-Cu 2+ The mass ratio of cyclooxygenase-2 is 3 to 8 × 10^ 3 :
1.
10. Use of the material for screening cyclooxygenase-2 inhibitors according to claim 1 or 2, or the material for screening cyclooxygenase-2 inhibitors obtained by the preparation method according to any one of claims 3 to 9 in screening cyclooxygenase-2 inhibitor materials, or in screening cyclooxygenase-2 inhibitor materials in combination with chromatography.